The survival benefits of adjuvant radiotherapy for malignant meningioma: a retrospective cohort study - Yuriz Bakhtiar; Fariz Eka Setiawan; Rafi Ilmansyah; Krisna Tsaniadi Prihastomo; Dody Priambada; Faiza Rizky Aryani Septarina; Muhamad Thohar Arifin; Zainal Muttaqin (Universa Medicina, 2025)
BackgroundMalignant meningiomas (MM) are rare aggressive tumors associated with poor survival outcomes. Due to their rarity, there is limited data on the outcomes and prognostic factors of MM patients, particularly on adjuvant radiotherapy roles in this tumor population. This study aims to investigate the clinical characteristics, prognostic factors, and survival outcomes of MM with focus on survival benefits of adjuvant radiotherapy. MethodsThis retrospective cohort study analyzed 19 MM patients, who were initially subjected to postoperative radiotherapy, at Dr. Kariadi General Hospital, Semarang, from 2013 to 2023. Kaplan-Meier analysis was used to estimate survival rates at 1, 2, and 5 years. Univariate and multivariate Cox regression analyses were performed to identify factors associated with overall survival (OS). Variables with a p-value ≤ 0.25 in univariate analysis were included in the multivariate models. ResultsThe median OS was 16 months (95% CI 0.0–40.2), with estimated 1-year, 2-year, and 5-year survival rates of 52.6%, 42.1%, and 15.8%, respectively. Adjuvant radiotherapy (RDT) was associated with a significantly improved OS (p<0.001). However, sex, age, tumor location, and extent of resection did not show a significant association with OS. Cox regression showed that RDT had no statistically significant effect on OS in the multivariate model (HR = 0, 95% CI 0–1.8, p=0.923). ConclusionAdjuvant radiotherapy is critical for improving OS in MM patients, and gross-total resection (GTR) alone does not guarantee better long-term outcomes. Further studies with larger cohorts and molecular analysis are necessary to refine treatment strategies for MM.